PENGARUH PROFITABLITIAS, KEPEMILIKAN MANAJERIAL, DAN UKURAN DEWAN DIREKSI TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN RESTAURANT, HOTEL, DAN TOURISM - Siswoko, Sherina Laurencia; Atmini Susilandari , Caecilia (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2023)
This quantitative research aims to analyze the influence of profitability, managerial ownership, and board size on financial distress in 31 restaurants, hotels, and tourism companies. The research used secondary data from Indonesian Stock Exchange in 2019-2021. The total sample is 93 data obtained by purposive sampling method. Profitability variable is measured by return on assets (ROA), managerial ownership variable is measured by the percentage of managerial ownership, and the number of boards variable is measures by board size. The dependent variable is financial distress, measured by the interest coverage ratio (ICR). Data Analysis used descriptive statistics and logistic regression. The analytics tools used SPSS 26.0 version. The result shows profitability has a negative significance on a company's propensity to get financial distress. At the same time, managerial ownership and board size are insignificant to a company's propensity to get financial distress. Keywords: financial distress, profitability, managerial ownership, board size